Beginning powerShell for SharePoint 2013 - Charlebois-Laprade, Nikolas (Apress, 2014)
Beginning PowerShell for SharePoint 2013 is a book for the SharePoint administrator looking to expand his or her toolkit and skills by learning PowerShell, Microsoft's vastly flexible and versatile object oriented scripting language. PowerShell is the future of Microsoft administration, and SharePoint is a complex product that can be managed more easily and quickly with PowerShell cmdlets and scripts. This book helps bridge the gap, introducing PowerShell fundamentals and operations in the context of deploying, migrating, managing, and monitoring SharePoint 2013. Author Nik Charlebois-Laprade begins by explaining the fundamental concepts behind the PowerShell language. Then, with copious real-world examples and scripts, he lays the foundation for PowerShell novices to automate interactions with the various pieces and components of the SharePoint 2013 platform. For SharePoint administrators wanting to do more with the technology, or for SharePoint developers trying to build their skills on the administration side, Beginning PowerShell for SharePoint 2013 is the perfect book to kick off your PowerShell journey.